Chemical Reactions of Indole Alkaloids That Enable Rapid Access to New Scaffolds for Discovery - Leas, Derek A.; Schultz, Daniel C.; Huigens III, Robert W. (SynOpen, 2023)
This graphical review provides a concise overview of indole alkaloids and chemical reactions that have been reported to transform both these natural products and derivatives to rapidly access new molecular scaffolds. Select biologically active compounds from these synthetic efforts are reported herein.
Keywords: indole alkaloids; yohimbine; vincamine; reserpine; chemical synthesis; ring distortion